2019
DOI: 10.1096/fj.201901712r
|View full text |Cite
|
Sign up to set email alerts
|

Lithium targeting of AMPK protects against cisplatin‐induced acute kidney injury by enhancing autophagy in renal proximal tubular epithelial cells

Abstract: Autophagy has been demonstrated to be vital for kidney homeostasis and is centrally implicated in the pathogenesis of cisplatin-induced acute kidney injury (AKI). Lithium is a potent autophagy inducer in a number of cell types. However, it remains uncertain whether its autophagic activity is associated with a beneficial effect on renal tubular cells in AKI. This study aimed to examine the effect of lithium on renal autophagy in cisplatin-induced AKI. Mice or renal proximal tubular epithelial cells in culture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 57 publications
3
23
1
Order By: Relevance
“…The AMPK/mTOR signaling pathway has emerged as a crucial regulator of autophagy (Kim et al, 2011;Kim et al, 2016). AMPK activation generally plays a protective role in various renal injury models (Allouch and Munusamy, 2017;Bao et al, 2019;Liu et al, 2019b). Recently, DEX has been confirmed to exert protective effects by activating AMPK and suppressing inflammatory responses (Wang et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…The AMPK/mTOR signaling pathway has emerged as a crucial regulator of autophagy (Kim et al, 2011;Kim et al, 2016). AMPK activation generally plays a protective role in various renal injury models (Allouch and Munusamy, 2017;Bao et al, 2019;Liu et al, 2019b). Recently, DEX has been confirmed to exert protective effects by activating AMPK and suppressing inflammatory responses (Wang et al, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-induced AKI seriously threatens the health of cancer patients and largely limits its application to chemotherapy [26]. Therefore, it is of great signi cance to study the pathogenesis of cisplatin-induced AKI.…”
Section: Resultsmentioning
confidence: 99%
“…As such, maltol play a protective role in cisplatin nephrotoxicity through AMPK/PI3K/AKT and p53 pathways (Mi et al, 2018). Lithium is a validated autophagy inducer with potent efficacy (Bao et al, 2019). Bao et al (2019) suggested that Lithium protect renal tubular cells against cisplatin nephroxicity.…”
Section: Targeting Ampk For Therapy In Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…Lithium is a validated autophagy inducer with potent efficacy (Bao et al, 2019). Bao et al (2019) suggested that Lithium protect renal tubular cells against cisplatin nephroxicity. Lithium activated and phosphorylated AMPKα to enhance autophagy to protect cell following cisplatin treatment both in vitro and in vivo.…”
Section: Targeting Ampk For Therapy In Cisplatin Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation